Impacto do uso de espécies de cobertura na estrutura de um Latossolo Argiloso e seus reflexos no rendimento de grão de milho - Villa, Bruna de (2020)
The present work aimed to evaluate the effect of cover species and changes in the management of the no-tillage system on the structure of a clayey Oxisol and its reflexes on corn productivity. The experimental design used was completely randomized with 4 repetitions for the physical characterization of the soil and three repetitions for corn productivity. The data of physical attributes, before and after the use of cover species / changes in the no-tillage system, were analyzed as a factorial model, having seen the effects of cover species and seasons. The treatments consisted of three plots involving management changes in the no-tillage system: traditional no-tillage system (control), scarified no-tillage system and plastered no-till system and twelve other plots involving the cultivation of vegetation cover species, six species with summer vegetation cover: pearl millet (Pennisetum americanum), crotalaria juncea (Crotalaria juncea), dwarf pigeon (Cajanus cajan), crotalaria spectabilis (Crotalaria spectabilis), guandú bean (Cajanus Cajan), black mucuna (Mucuna Pruriens) and other six plots with winter vegetation cover species: white oats (Avena sativa), black oats (Avena strigosa), rye (Secale cereale), forage vetch + black oats (Pisum sativum var. arvense + Avena strigosa), white lupine + black oats (Lupinus albus + Avena strigosa), forage turnip + black oats (Brassica rapa L. + Avena strigosa). The experiment was carried in experimental plots of 20 x 16 m. Undisturbed soil samples were collected in layers 0-0.1; 0.1-0.2 and 0.2-0.3 m, before and after cultivation, corn, where density, porous space and hydraulic conductivity of the saturated soil were evaluated. The corn grain yield was evaluated in 13.5 m² subplots. The treatment means were compared by the Scott Knott test at 5% significance. The treatments of crotalaria spectabilis, black mucuna, white oats and black oats + white lupine were the ones that provided improvements in the soil structure. As for the grain yield of the corn crop, the treatments of millet, dwarf pigeon, crotalaria júncea, guandú bea, crotalaria spectabilis, white oats, rye, black oats + turnip, black oats + white lupine, scarified no-till system, no-tillage system with plaster and traditional no-tillage system provided the highest grain yield in relation to the other treatments.